Frequency of Postpartum Hemorrhage following Oxytocin use during Labor - Safia Yasmin, Noreen Nasim, Ayesha Munawar, Sadia Shakir, Amna Saeed, Rizwan Sadiq (Pakistan Journal of Medical & Health Sciences, 2022)
Post-partum hemorrhage is one of the major causes of maternal morbidity and mortality worldwide. Efficient and timely management of 3rd stage of labor decreases the loss of blood and reduces the chances of hemorrhage. Prophylactic use of oxytocics plays a key role in the management of 3rd stage of labor. Use of xytocin for augmentation of labor is itself a risk factor for post-partum hemorrhage. This study was designed to find frequency of postpartum hemorrhage following oxytocin use during labor. Objective: To determine frequency of postpartum hemorrhage following oxytocin use during labor. Methodology: It was a Descriptive case control study. Cases were those patients in whom postpartum hemorrhage observed after delivery. Controls were those patients in whom in whom postpartum hemorrhage was not observed after delivery. In both cases and controls, it was observed whether oxytocin was used for augmentation of labor or not. In both groups, frequency of PPH was observed following oxytocin use during labor. Study was conducted in labor ward of Department of Obstetrics & Gynaecology, Sheikh Zayed Hospital, Rahim Yar Khan from 18th June 2018 to 17th December 2018. Results: Mean age of the patients was 27.60±0.19 vs. 27.39±0.20 years respectively in Cases and Controls. Mean gestational age was 38.46±0.05 vs. 38.54±0.06 weeks in Cases and Controls respectively. Oxytocin use was observed in 130(53.28%) vs. 106(43.44%) among Cases and Controls respectively. Conclusion: There is almost 1.5 times increased risk of having post-partum hemorrhage in patients having augmentation with oxytocin during labor.